Physician–Patient Language Discordance and Poor Health Outcomes: A Systematic Scoping Review - Cano-Ibáñez, Naomi; Zolfaghari, Yasmin; Amezcua-Prieto, Carmen; Khan, Khalid Saeed (Frontiers in Public Health, 2021)
Objective: This systematic review assessed whether physician-patient language concordance, compared with discordance, is associated with better health outcomes. Methods: A systematic literature search was conducted, without language restrictions, using Pubmed, Embase, Web of Science and PsycINFO, from inception till July 2020. We included studies which evaluated the effects of physician-patient language concordance on health outcomes. Articles were screened, selected, and data-extracted in duplicate. Review protocol was prospectively registered (PROSPERO, CRD42020157229). Results: There were 541 citations identified through databases and 8 through reverse search and Google Scholar. A total of 15 articles (84,750 participants) were included reporting outcomes within five domains: diabetes care (4 studies), inpatient care (5 studies), cancer screening (3 studies), healthcare counselling (2 studies) and mental health care (1 study). Ten studies were of good quality, four were fair and one was poor, according to the modified Newcastle-Ottawa Scale. Eight studies (53%) showed a significant negative association between language discordance and at least one clinical outcome. Five studies (33%) found no association. Conclusion: Over half the evidence collated showed that physician-patient language concordance was associated with to quantitatively better health clinical outcomes.